Floriferous herbaceous and substrates for use on extensive green roofs - Dos Santos, Patrick Luan Ferreira [UNESP]; De Castilho, Regina Maria Monteiro [UNESP] (Lepidus Tecnologia, 2018)
De maneira geral, os telhados verdes extensivos são definidos como toda cobertura revestida de vegetação herbácea e substrato superficial, entretanto, no Brasil são poucas as informações referentes aos materiais para instalação e manutenção desses sistemas, sendo essencial a busca de melhores espécies e substratos adaptados as condições tropicais. Assim, objetivou-se avaliar o desempenho de herbáceas floríferas e substratos para uso em telhados verdes extensivos. O experimento foi realizado em campo e a pleno sol, em recipientes de plástico preto (8,46 L e 15,5 cm de altura), elevados a 90 cm do chão, em um esquema fatorial 3x2, sendo 3 espécies floríferas herbáceas (Torênia var. Kauai, Vinca var. Pacifica XP e Petúnia var. Bacopa) e 2 substratos [S1-Carvão vegetal + casca de pinus + turfa + vermiculita expandida (1v:1v:1v:1v) e S2- Fibra de coco + casca de arroz carbonizado + turfa + vermiculita expandida (1v:1v:1v:1v)], com 3 repetições por tratamento. Avaliou-se nos substratos: pH, condutividade elétrica, macro e microporosidade, porosidade total, densidade e capacidade de retenção de água. Para o desempenho das espécies, após 60 dias da instalação do experimento, foram avaliados: teor de clorofila das folhas, número de flores e temperatura superficial da vegetação. Observou-se que o substrato S2, apresentou os melhores resultados nas análises físico-químicas, e isso possivelmente veio a refletir no desempenho das espécies, sendo que Torênia quando cultivada nesse substrato, apresentou o maior teor de clorofila (42,67 SPAD). O número de flores foi estatisticamente igual para Torênia e Vinca em ambos substratos, já as três herbáceas floríferas apresentaram diminuição da temperatura superficial. Dessa forma, recomenda-se para uso em telhados verdes extensivos o substrato composto de Fibra de coco + casca de arroz carbonizado + turfa + vermiculita expandida (1v:1v:1v:1v), e a herbácea florífera Torênia var. Kauai.

In general, extensive green roofs are defined as all cover covered with herbaceous vegetation and surface substratum, however, in Brazil there are few information regarding the materials for installation and maintenance of these systems, being essential the search for better species and substrates adapted to the tropical conditions. Thus, the objective was to evaluate the performance of floriferous herbaceous and substrates for use in extensive green roofs. The experiment was carried out in the field and in full sunlight, in black plastic containers (8.46 L and 15.5 cm high), elevated 90 cm from the ground, in a 3x2 factorial scheme. Being 3 herbaceous floriferous species (Torenia var. Kauai, Periwinkle var. Pacifica XP and Petunia var. Bacopa) and 2 substrates [S1-Charcoal + pine bark + peat + expanded vermiculite (1v:1v:1v:1v) and S2- Coconut fiber + carbonized rice husk + peat + expanded vermiculite (1v:1v:1v:1v)], with 3 replicates per treatment. It was evaluated in the substrates: pH, electrical conductivity, macro and microporosity, total porosity, density and water retention capacity. For the development of the species, 60 days after the experiment installation, were evaluated, chlorophyll content of leaves, number of flowers and vegetation surface temperature. It was observed that the substrate S2 presented the best results in the physico-chemical analyzes, and this possibly came to reflect on the performance of the species, and that Torenia when cultivated in this substrate had the highest chlorophyll content (42.67 SPAD). The number of flowers was statistically the same for Torenia and Periwinkle in both substrates, while the three floriferous herbaceous plants showed a decrease in surface temperature. Thus, it is recommended for use on extensive green roofs the substrate composed of coconut fiber + carbonized rice husk + peat + expanded vermiculite (1v:1v:1v:1v), and the floriferous herbaceous Torenia var. Kauai.
Keywords: Catharanthus roseus; Petunia x hybrid; Petunia x hybrida; Physical-chemical properties; Propriedades físico-química; Torenia fournieri